The Existence of Self-Enforcing Implicit Contracts - Bull, Clive (Quarterly Journal of Economics, 1987)
Implicit contracts are nontrivial Nash equilibria to the post-hiring trading game between a worker and the employer. These are supported by intrafirm, rather than labor market, reputations. The existence of an implicit contract that supports efficient trade is proved in a simple model.